4.1 AMIPROM: A Pilot RCT on Serial Transabdominal Amnioinfusion Versus Expectant Management in Very Early PROM (ISRCTN 8192589). (26th April 2013) - Roberts, D; Vause, S; Martin, W; Green, P; Walkinshaw, SA; Bricker, L; Beardsmore, CS; Shaw, NJ; McKay, A; Skotny, G; Williamson, P; Alfirevic, Z
Abstract : Objective: a randomised controlled multicentre pilot study to assess: - short- and long-term outcomes and data to inform a larger, definitive clinical trial. - the feasibility of recruitment and the retention through to long term follow up of participants with very early rupture of membranes. Participants: Women with singleton pregnancies and confirmed preterm prelabour rupture of membranes between 16 +0 and 24 +0 weeks gestation. Women with fetal abnormality or obstetric indication for immediate delivery were excluded. Interventions: Participants were randomly allocated to either serial weekly trans-abdominal amnioinfusions when the deepest pool of amniotic fluid was less <2 cms or expectant management. Results: 58 pregnancies recruited: 28 in the amnioinfusion group (AI); 28 in the expectant management group (exp); two post-randomisation exclusions. Overall perinatal survival in both groups was 17/56. Mean gestational age for AI group was 28.4 weeks vs. 29.8 weeks for exp (mean SD-1.4, 95% CI –0.2–1.5). One case of severe maternal sepsis requiring admission to HDU in the expectant management arm. Overall chance of surviving without long-term respiratory or neurodevelopmental disability is 7.1%; 4/28 (14%) in the AI group and 0/28 in the exp group (RR 9.0; 95% CI 0.51, 159.70). Conclusions: The pilot findings do not suggest that clinicians should alter the current practise of expectantly managing rupture of membranes between 16 + 0 and 24 + 0 weeks of pregnancy. A larger definitive study to evaluate whether amnioinfusion has a cost-effective and acceptable role in improving healthy survival in very early rupture of membranes indicated. Funding: NIHR HTA programme.